1998
DOI: 10.1128/jvi.72.2.1052-1059.1998
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Neutralizing Antibodies to T-Cell Line-Adapted and Primary Human Immunodeficiency Virus Type 1 Isolates with a Prime-Boost Vaccine Regimen in Chimpanzees

Abstract: Five chimpanzees were immunized by administration of one or more intranasal priming doses of one to three recombinant adenoviruses containing a gp160 insert from human immunodeficiency virus type 1 (HIV-1) MN (HIV-1MN) followed by one or more boosts of recombinant HIV-1SF2 gp120 delivered intramuscularly with MF59 adjuvant. This regimen resulted in humoral immune responses in three of five animals. Humoral responses included immunochemically active anti-HIV-1 antibodies (Abs) directed to recombinant gp120 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The surface antigens of human immunodeficiency virus type 1 (HIV-1) have been the primary targets in attempts to develop an AIDS vaccine in the last decade (24,54). The efficacy of envelope-based vaccines has been demonstrated largely in the chimpanzee model against tissue culture-adapted viruses such as HIV-1 IIIB (10,11,15,26,43,57) and SF2 (14,22). Infection by these virus isolates is generally self-limiting and does not lead to AIDS-like diseases.…”
mentioning
confidence: 99%
“…The surface antigens of human immunodeficiency virus type 1 (HIV-1) have been the primary targets in attempts to develop an AIDS vaccine in the last decade (24,54). The efficacy of envelope-based vaccines has been demonstrated largely in the chimpanzee model against tissue culture-adapted viruses such as HIV-1 IIIB (10,11,15,26,43,57) and SF2 (14,22). Infection by these virus isolates is generally self-limiting and does not lead to AIDS-like diseases.…”
mentioning
confidence: 99%
“…For example, the level of intercellular cell adhesion molecule type 1 (ICAM-1) on a virus particle affects the sensitivity with which it can be neutralized by antibody (15,40). Sawyer et al (43), using laboratory-adapted and primary isolates, showed that the host cells used for growing the virus stock influenced the sensitivity of the virus to neutralization and that the type of target cells used in the neutralization assay, i.e., T-cell lines or unstimulated or phytohemagglutinin (PHA)-activated peripheral blood mononuclear cells (PBMCs), also contributes to the sensitivities with which neutralization of HIV and other viruses is detected (34,53,54).…”
mentioning
confidence: 99%
“…Taken together, the results indicated that this macaque possessed a strong, broad antibody response which likely contributed to its slower disease progression. Antibody responses have been shown to play a role in protection of chimpanzees against HIV infection (7,14,20,41,57,68). In the macaque system, they have been shown to participate in morerapid viral clearance (27).…”
Section: Discussionmentioning
confidence: 99%